Current and Novel Therapies for Cluster Headache: A Narrative Review - Bruna de Freitas Dias; Christopher L. Robinson; Maria Dolores Villar-Martinez; Sait Ashina; Peter J. Goadsby (Pain and Therapy)
Abstract Cluster headache (CH) is an excruciating and debilitating primary headache disorder. The prevalence is up to 1.3%, and the typical onset is around age 30. Often misdiagnosed as migraine, particularly in children, the diagnosis rate of CH has been increasing among women. CH is characterized by intense unilateral pain and autonomic symptoms, significantly impacting patients’ quality of life, mental health, and productivity. Genetic associations suggest a familial risk for developing CH, with lifestyle factors also potentially playing a role. The pathophysiology involves alterations in both central and peripheral nervous system, with the hypothalamus, trigeminocervical complex, and neuropeptides such as calcitonin gene-related peptide (CGRP) being implicated. Nonpharmacological treatments focus on patient education and lifestyle modifications, while pharmacological treatments include acute therapies such as oxygen and subcutaneous or nasal sumatriptan, as well as preventive therapies like verapamil, lithium, and CGRP monoclonal antibodies. Transitional options include oral corticosteroids and greater occipital nerve injections. Emerging interventional procedures offer new avenues for managing refractory cases. Noninvasive vagal nerve stimulation and occipital nerve stimulation show promise for both acute and preventive treatment. Careful consideration of safety profiles is crucial in specific populations such as pregnant patients and children. Current treatments still leave patients highly burdened by limited efficacy and side effects. Future research continues to explore novel pharmacological targets, interventional procedures, and the potential role of psychedelics in CH management. Comprehensive, multifaceted treatment strategies are essential to improve the daily functioning and quality of life for individuals with CH.